Solution-Processed All-Solid-State Electrochromic Devices Based on SnO2/NiO doped with Tin - Gieun Kim (MDPI AG, 2021)
We investigated the photochromic (PC) and electrochromic (EC) properties of tin-doped nickel oxide (NiO) thin films for solution-processable all-solid-state EC devices. The PC effect is shown to be enhanced by the addition of Sn into the precursor NiO solution. We fabricated an EC device with six layers—ITO/TiO2 (counter electrode)/SnO2 (ion-conducting layer)/SiO2 (barrier)/NiO doped with tin (EC layer)/ITO—by a hybrid fabrication process (sputtering for ITO and TiO2, sol–gel spin coating for SnO2 and NiO). The EC effect was also observed to be improved with the Sn-doped NiO layer. It was demonstrated that UV/O3 treatment is one of the critical processes that determine the EC performance of the hydroxide ion-based device. UV/O3 treatment generates hydroxide ions, induces phase separation from a single mixture of SnO2 and silicone oil, and improves the surface morphology of the films, thereby boosting the performance of EC devices. EC performance can be enhanced further by optimizing the thickness of TiO2 and SiO2 layers. Specifically, the SiO2 barrier blocks the transport of charges, bringing in an increase in anodic coloration. We achieved the transmittance modulation of 38.3% and the coloration efficiency of 39.7 cm2/C. We also evaluated the heat resistance of the all-solid-state EC device and found that the transmittance modulation was decreased by 36% from its initial value at 100 °C. Furthermore, we demonstrated that a large-area EC device can be fabricated using slot-die coating without much compromise on EC performance.